PENINGKATAN AKTIVITAS PEMBELAJARAN DENGAN MENGGUNAKAN METODE BERMAIN PERAN - Bintang, Risde; ., Marzuki; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Common problem of this research is "whether the role playing method can improve student learning activities fourth grade elementary school in Sungai Raya 46 Citizenship Education learning?" Objective studies to provide information and clarity regarding the actual improvement of student learning activities in the classroom teaching Citizenship Education IV. The method used is descriptive method. The subjects were teachers of Citizenship Education and Elementary School fourth-grader State 46 Sungai Raya. Setting research in the classroom setting. Techniques used direct observation techniques. While the data collection tool is the observation sheet. The data collected is data about the activities of teachers and students in the learning process.The results of physical activity on average 66.5% in the first cycle to 80.5% in the second cycle. Average of 59.2% of mental activity in the first cycle to 81.4% in the second cycle. Average of 68.4% emotional activity in the first cycle to 81.4% in the second cycle. Based on the above results it can be concluded that the increased activity bejalar to play a role in the learning method Citizenship Education can increase physical activity by 14%, 22.2% mental activity, emotional activity of 13%. Based on these conclusions, it can be concluded that the method can be used as an alternative to play a role in improving student learning activity. Keywords: Activity, learning and role playing method. Abstrak: Tujuan penelitian untuk memberikan informasi dan kejelasan yang aktual mengenai peningkatan aktifitas belajar murid dalam pembelajaran Pendidikan Kewarganegaraan kelas IV. Metode yang digunakan adalah metode deskriptif. Subjek penelitian ini adalah guru yang mengajar Pendidikan Kewarganegaraan dan murid kelas IV Sekolah Dasar Negeri 46 Sungai Raya. Setting penelitian setting dalam kelas. Teknik yang digunakan teknik observasi langsung. Sedangkan alat pengumpul datanya adalah lembar observasi. Data yang dikumpulkan adalah data tentang aktivitas guru dan murid dalam proses pembelajaran. Hasil penelitian rata-rata aktivitas fisik 66,5% di siklus I menjadi 80,5% di siklus II. Rata-rata aktivitas mental 59,2% di siklus I menjadi 81,4% di siklus II. Rata-rata aktivitas emosional 68,4% di siklus I menjadi 81,4% di siklus II. Berdasarkan hasil di atas dapat disimpulkan bahwa peningkatan aktivitas bejalar dengan metode bermain peran dalam pembelajaran Pendidikan Kewarganegaraan dapat meningkatkan aktivitas fisik sebesar 14%, aktivitas mental 22,2%, aktivitas emosional 13%. Berdasarkan kesimpulan tersebut maka dapat disimpulkan bahwa metode bermain peran dapat dijadikan alternatif dalam meningkatkan aktivitas belajar murid. Kata kunci : Aktifitas, belajar dan metode bermain peran.